Ecological Restoration of Ban Mae Keymook Community, Tambon Ban Tub, Mae Cheam District, Chiang Mai Province with Dye Plants and Natural Dyeing for Leveraging Local Textile Products - Sutakcom, Oranoot; Komolsirichok, Yanisa (Recent Science and Technology, 2021)
The objectives of this research were 1) to gather knowledge on dye plants in the community, 2) to develop natural dyeing process from local natural materials for hand-woven pattern work of the community, 3) to study the durability of natural dyes to light and for washing, 4) to design and develop hand-woven textile products from unique natural colors of the community, 5) to design the product tag that can promote community marketing, and 6) to promote planting dye plants for natural dyeing. This study investigated pigment from dyes plants in Ban Mae Kee Mook community, Ban Thap sub-district, Mae Chaem district, Chiang Mai Province Natural dyes technique was used and durability testing was employed prior to product development and marketing testing. The results of research found that 14 kinds of dyes plants were found in Ban Mae Knee Mook. They provided 5 color shades: red - pink, yellow, green, orange and brown. The color fastness to artificial light and to washing was at level 4 which was acceptable according to Community Products Standards, except dyes from Anatto, Sappan and Alum tree. The natural dyed yarns were woven with traditional pattern and arranged in new elements. Then, the products were designed under the concept "Adding value of woven fabric to make fashionable and contemporary style products to urban context". The products consisted of clothes with different six applied pattern and bags with three contemporary styles where the products met the requirement of cultural-product consumers. The product tag was designed for recall and re-purchase purposes. Moreover, planning for planting more dye plants in the community were developed for future dyeing. Therefore, if the community continues planting dye plants and stops cutting, the community’s ecosystem will be completely restored.